Vitamin A cassava in Nigeria: Crop development and delivery - Ilona, Paul; Bouis, Howarth E.; Palenberg, M.; Moursi, Mourad; Oparinde, Adewale (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Biofortified vitamin A “yellow” cassava can help address the adverse health effects of vitamin A deficiency. By 2016, HarvestPlus and its partners had successfully developed and delivered vitamin A cassava varieties to more than one million farming households in Nigeria and the Democratic Republic of Congo (DRC). HarvestPlus has established the proof of concept that vitamin A cassava varieties can be developed without compromising yield levels and that these varieties are widely accepted. The delivery program has shown that farmers are willing to grow vitamin A cassava varieties and consumers are willing to buy and eat vitamin A cassava products. This paper summarizes the country, nutritional and consumer background, the crop development and release of biofortified vitamin A cassava varieties in Nigeria, progress in monitoring and evaluation of results, and synthesizes lessons learned and future challenges.